Адвентизація рослинності як наслідок спонтанної та цілеспрямованої інтродукції рослин - Maryushkina, V.Y. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2002)
The influence of spontaneously and purposefully introduced specios of plants on the ecosystems was considered. It was shown that adventization of vegetation take place on background of the destruction of the natural plants cover and the abolition of the system of the feedback. The intraspecific variety plays the important role at the domination of the adventive species in the destroyed natural plant localities. The ways of successional processes control at the artoecosystems (agriculture, urban ecosystems, botanical gardens et al.) it was discussed.